PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENGELOLAAN BISNIS RITEL - Latifah Cahyani; Corry Yohana; Kusworo (STKIP Subang, 2026)
This research aims to determine the feasibility and practicality of developing interactive multimedia for the Retail Business Management subject for Grade XI students. The interactive multimedia was designed using an interactive and contextual approach by integrating multimedia elements such as videos, audio, images, and interactive quizzes to enhance students' active engagement in learning the Retail Business Management subject. This research employed the Research and Development (R&D) method using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The study was conducted at SMK Negeri 50 Jakarta with Grade XI Retail Business students. The results of the development indicate that the learning media can improve students' learning motivation. The implementation and testing of the learning media at SMK Negeri 50 Jakarta demonstrated its effectiveness in enhancing students' learning motivation in the Retail Business Management subject. The use of this learning media is expected to address the limited availability of instructional media in schools while also increasing students' engagement in the learning process.